Serum total testosterone in eumenorrhoeic young Bangladeshi women - Banu, Hurjahan; Morshed, Md Shahed; Sultana, Tania; Zamila, Begum Moriom; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Population and an assay-specific cut-off value of total testosterone (TT) is required to diagnose different conditions with mild hyperandrogenemia in females of reproductive age. Objective: To determine the serum TT cut-off limits for eumenorrhoeic women and to assess whether testosterone levels alter as individuals age and BMI change. Methods: This cross-sectional study initially included 251 healthy eumenorrhoeic women between the ages of 16 and 35 who gave written, informed consent. Pregnancy, breastfeeding, history of smoking or alcohol intake, history of oral contraceptives within three months of enrollment (n=2), and having significant hirsutism (modified Ferriman-Gallwey score ≥8) or acne (n=5) were excluded. Venous blood was collected to measure alanine aminotransferase (ALT), creatinine, thyroid stimulating hormone, prolactin, and total testosterone. All the hormones were measured by the chemiluminescent microparticle immunoassay. Four participants were excluded for impaired renal and liver function. Any participant having impaired thyroid function (n= 4), hyperprolactinemia (n=4), and very high TT value (n=2) were also excluded. A total of 230 healthy participants were included in the final analysis. The average TT level of the healthy population was calculated by mean±2×SEM. The values between 25th and 75th were considered as reference ranges for healthy women. Results: The mean±SD of age and BMI of the study population were 24.63±4.17 years and 22.44±3.69 kg/m2 respectively. The mean serum total testosterone was 25.50±1.36 (23.82 – 27.18) ng/dL. The 25th percentile and 75th percentile of TT were 17.50 ng/dL and 33.72 ng/dL respectively. Serum TT had inverse but insignificant associations with age and BMI. Conclusions: The reference range of TT in eumenorrhoeic young Bangladeshi women may be considered between 18.0 ng/dL and 34.0 ng/dL. The study findings might provide clinicians with baseline data for detecting hyperandrogenic conditions in young reproductive-age women. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2022; 1 (2): 44-49